PROFIL TINGKAT PENDIDIKAN MASYARAKAT DI KECAMATAN BASA AMPEK BALAI KABUPATEN PESISIR SELATAN - Putra, Riko Andika; Bakaruddin, Bakaruddin; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
Equity and expanding access to education focused on efforts to expand the capacity of educational units in accordance with national priorities and provide equal opportunities for all learners from various segments of society. This study aims to determine the level of public education in the Basa Ampek Balai Pesisir Selatan region which includes: 1) the level of public education, 2) accessibility, and 3) the capacity of the school .This research is descriptive. The population in this study population was all families (KK) in the Basa Ampek Balai Pesisir Selatan region, amounting to 7.458 households. Samples were taken in two ways, the sample areas were taken by purposive sampling technique, which is based on the location of the regional elections, the first villages are situated on the main road and 1 villages are located far from the main road, while the sample of respondents drawn with proportional random sampling technique with proportion of 15 % so that the population of 93 families.The research found that: (1) The level of public education in Pasar Tapan village including evolving and the level of public education in Sei Gambir Sako Tapan village including evolving. This suggests that the level of public education in the Basa Ampek Balai Pesisir Selatan region is not determined by the location of the area, (2) accessibility village in the Basa Ampek Balai Pesisir Selatan region, the road is asphalt, the main transport motorcycles, average home range 25 - 50 m from the highway. Distance to schools within range of educational services, namely 250 m for SD, 500-1 km for junior high and 2-5 km for high school and (3) The capacity of schools in Pasar Tapan village and Sei Gambir Sako Gambir Tapan village are ideal because the number of local available, the number of teachers and the number of registrants balanced so that the school -age population can be accommodated by the school facilities are available